1990
DOI: 10.1104/pp.92.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Large Subunit of Ribulose 1,5-Bisphosphate Carboxylase/Oxygenase as a Substrate for Transglutaminase in Medicago sativa L. (Alfalfa)

Abstract: Extracts prepared from floral meristematic tissue of alfalfa (Medicago sativa L.) were investigated for expression of the enzyme transglutaminase in order to identify the major protein substrate for transglutaminase-directed modifications among plant proteins. The large polymorphic subunits of ribulose 1,5-bisphosphate carboxylase/oxygenase in alfalfa, with molecular weights of 52,700 and 57,600, are major substrates for transglutaminase in these extracts. This was established by: (a) covalent conjugation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
4

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 27 publications
6
51
0
4
Order By: Relevance
“…PAs are involved in photosynthetic functions (Margosiak et al, 1990). In the present work, supplied exogenous Put significantly increased contents of chlorophyll a, carotenoid, and total chlorophyll, compared with the non-Put treatment (Tab.…”
Section: Chlorophyllsupporting
confidence: 58%
“…PAs are involved in photosynthetic functions (Margosiak et al, 1990). In the present work, supplied exogenous Put significantly increased contents of chlorophyll a, carotenoid, and total chlorophyll, compared with the non-Put treatment (Tab.…”
Section: Chlorophyllsupporting
confidence: 58%
“…Chloroplast TGases (ChlTGases) are different from those of the cytoplasm and are active in chloroplasts of both higher and lower plants. 20,27,51,57,58 Having as substrates the antenna complexes and Rubisco, 26,27 they are possibly involved in photosynthesis. The decrease in total TGase activity during petal senescence could thus be partly related to the breakdown of chloroplasts.…”
Section: Corolla Of Undetached¯owersmentioning
confidence: 99%
“…actin and tubulin 24 or cell wall proteins, 21 and through its involvement in the polymerisation of Rubisco. 26 Different roles for TGase have been proposed in chloroplasts 27 and mitochondria. 28 In contrast to the considerable number of reports concerning TGase in dying animal cells, no information is available regarding this enzyme family during PCD in plants.…”
Section: Introductionmentioning
confidence: 99%
“…In plant cells, the roles of TGases are similar to those in animal cells, in terms of several biochemical features, however, their presence in particular plant compartments and their substrates suggest that they may fulfil additional roles. TGases were found in the chloroplasts of several higher plants and some algae, where they possibly stabilize and protect antenna complexes and Rubisco, thus possibly being involved in the regulation of the photosynthetic process (Margosiak et al, 1990;Della Mea et al, 2004b;for review, see Serafini-Fracassini and Del Duca, 2002). In some lower organisms, like Chlamydomonas (Waffenschmidt et al, 1999) and some fungi, TGase activity has been found in the cell walls, where the enzyme has a structural role or acts as the defense elicitors of higher plants (for review, see Del Duca and Serafini-Fracassini, 2005).…”
mentioning
confidence: 99%